2021
DOI: 10.1177/8756972820986660
|View full text |Cite
|
Sign up to set email alerts
|

A Routine Dynamics Lens on the Stability-Change Dilemma in Project-Based Organizations

Abstract: A central issue in project-based organizations (PBOs) is how to balance the need for flexibly responding to changing customer demands and creating consistent performance in the organization at large. This article discusses the relevance of a routine dynamics lens for understanding this dilemma. We show how routine dynamics might help to understand how and under what conditions routines—with their dual capacity for stability and change—produce a variety of performances, some stable and some varying, in the PBO.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
(155 reference statements)
0
5
0
Order By: Relevance
“…Paradoxes denote “persistent contradictions between interdependent elements” (Schad et al, 2016, p. 6) and are basic characteristics of organizational life (De Keyser et al, 2019). A wide array of organizational phenomena, including projects (Bygballe et al, 2021; Sabini & Alderman, 2021), are increasingly being investigated by paradox researchers, using different lenses to do so (see Gaim et al, 2018; Miron-Spektor, Ingram et al, 2018; Putnam et al, 2016). Schad et al (2016, p. 11) noted, “the core characteristics of paradox engender its persistence.” Thus, paradoxes have conceptually been viewed as being persistent, meaning they resist closure (Lewis, 2000; Smith & Lewis, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Paradoxes denote “persistent contradictions between interdependent elements” (Schad et al, 2016, p. 6) and are basic characteristics of organizational life (De Keyser et al, 2019). A wide array of organizational phenomena, including projects (Bygballe et al, 2021; Sabini & Alderman, 2021), are increasingly being investigated by paradox researchers, using different lenses to do so (see Gaim et al, 2018; Miron-Spektor, Ingram et al, 2018; Putnam et al, 2016). Schad et al (2016, p. 11) noted, “the core characteristics of paradox engender its persistence.” Thus, paradoxes have conceptually been viewed as being persistent, meaning they resist closure (Lewis, 2000; Smith & Lewis, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Second, this study demonstrated the merit of the routine dynamics lens in practice-based innovation studies at preadoption stages. In the previous literature, routine dynamics were already used to better understand how organizational change processes take place (Bygballe et al 2021;Danner-Schröder and Geiger 2016;Turner and Rindova 2012) but not specifically as a lens to study the microdynamics in innovation processes. The detailed and empirically rich descriptions gathered through the routine dynamics lens complement the individual behavioral change models of Davis (1986), Ajzen (1991), and Venkatesh and Bala (2008) that focus on an individual level but do not allow for a detailed analysis of performed practices and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Routines are repetitive, recognizable, and interdependent patterns of actions built around a mechanism of stability and change (Becker 2004;Feldman et al 2016). This dynamic, called the generative mechanism of stability and change, has been used in studies to better understand how organizational change processes take place (e.g., Bygballe et al 2021;Danner-Schröder and Geiger 2016;Turner and Rindova 2012), and may, in turn, help to describe how interacting thoughts and actions of professionals stabilize or reshape existing construction practices during technology adoption (Becker 2004;Feldman et al 2016). By using routine dynamics as a conceptual lens, the objective of this study is to develop an empirical conceptual model of early interactions between work processes of prospective users and new technology.…”
Section: Theoretical Points Of Departurementioning
confidence: 99%
“…All in all, it is necessary to examine the question of how interorganizational projects deal with the tension of legitimacy and flexibility in these complex institutional backdrops. The simultaneous exploration of the embeddedness of a project and project management practices may help to promote an improved understanding of the need to balance legitimacy-and-flexibility or stability-and-change tension and a better understanding of its impact on project performance (Bygballe et al, 2021).…”
Section: Theoretical Backgroundmentioning
confidence: 99%